ANALISIS TENTANG PERSEPSI ORANG TUA TERHADAP BELAJAR ONLINE DI SEKOLAH SE-KECAMATAN SINGKEP PESISIR, KABUPATEN LINGGA - Rahmahwati, Rahmahwati; Eddison, Ahmad; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was motivated by the difficulties of parents in helping and guiding children in learning at home during the Covid-19 pandemic. The formulation of the problem in this study is how are parents' perceptions of online learning in schools in the coastal Singkep District, Lingga Regency? The research objective was to find out how parents' perceptions of online learning in schools in Singkep Pesisir District, Lingga Regency. The benefit of the research results is that it becomes a source of learning for all parties, especially parents in responding to online learning that children undergo while at home. This research method is descriptive quantitative, the data collection instrument used in this study is a questionnaire consisting of 5 indicators with 24 questions. The population in this study were all parents of students in schools in the Singkep Pesisir District, Lingga Regency. The sample in this study was taken using a proportional sampling technique. Based on the results of the research conducted, it can be concluded that the overall data regarding parents' perceptions of online learning in schools throughout the Singkep Pesisir District, Lingga Regency is in the "Agree" category. Strongly Agree amounts to 13.42% plus the Agree results with the amount of 66.35%. that is, the sum is 79.77% with the presence in the range 68.01% - 84.00%. Thus, Parents' Perception of Online Learning in Schools in Singkep Pesisir District, Lingga Regency is "Good". Key Words: Perception, Parents, Online Learning.